GLP‐1 Receptor Agonists Alleviate Diabetic Kidney Injury via β‐Klotho‐Mediated Ferroptosis Inhibition - Shasha Tian; Saijun Zhou; Weixi Wu; Yao lin; Tongdan Wang; Haizhen Sun; A‐Shan‐Jiang A‐Ni‐Wan; Yaru Li; Chongyang Wang; Xiaogang Li; Pei Yu; Yanjun Zhao (Advanced Science)
Abstract Semaglutide (Smg), a GLP‐1 receptor agonist (GLP‐1RA), shows renal protective effects in patients with diabetic kidney disease (DKD). However, the exact underlying mechanism remains elusive. This study employs transcriptome sequencing and identifies β‐Klotho (KLB) as the critical target responsible for the role of Smg in kidney protection. Smg treatment alleviates diabetic kidney injury by inhibiting ferroptosis in patients, animal models, and HK‐2 cells. Notably, Smg treatment significantly increases the mRNA expression of KLB through the activation of the cyclic adenosine monophosphate (cAMP) signaling pathway, specifically through the phosphorylation of protein kinase A (PKA) and cAMP‐response element‐binding protein (CREB). Subsequently, the adenosine monophosphate‐activated protein kinase (AMPK) signaling pathway is activated, reprograming the key metabolic processes of ferroptosis such as iron metabolism, fatty acid synthesis, and the antioxidant response against lipid peroxidation. Suppression of ferroptosis by Smg further attenuates renal inflammation and fibrosis. This work highlights the potential of GLP‐1RAs and KLB targeting as promising therapeutic approaches for DKD management.